Applying feminist theories to women in science programs. - Rosser, Sue V. (Signs: Journal of Women in Culture & Society)
Examines feminist theories as they apply to women in science programs. Feminist theories' influence on disciplines such as the humanities; Scientists' involvement in using feminist theories to develop critiques of science; Mechanism for characterizing projects funded by the National Science Foundation under the Program for Women and Girls.